PEMBINAAN HOW TO BE OUTSTANDING MC AND MODERATOR DI KARANG TARUNA GARUDA VILLA HANG LEKIR BATAM - Zakrimal Zakrimal; Angel Purwanti; Riki Mohamad Aziz (ASOSIASI IDEBAHASA KEPRI, 2020)
English as a communication tool for people around the world because English is the International language. As a means of global communication, English must be actively mastered both oral and written. In this Community Service (PKM) Coaching Ability to speak in public (public speaking) is very important for teenagers or students so that in the future they are ready to face Batam as a free trade zone and MICE (Meeting, Incentive, Ceremonies, and Events). So that this Public Speaking training is very much needed by Karang Taruna Garuda so that Karang Taruna members can practice it in youth activities held in the housing complex. This training aims to increase the knowledge of Public Speaking and the ability of members of the youth to speak in public such as MC, Moderator in youth activities in the era of globalization and this MICE era.